MANAGEMENT DUALISM (TOP-DOWN AND MADRASAH-BASED MANAGEMENT) IN THE IMPLEMENTATION OF EDUCATIONAL SUBSIDY PROGRAMS FOR ORPHANS - Anis Fauzi; Nurdina Fitri; Mila Nuroniyah; Syifa Fauziyah El-Abida (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2025)
This study aims to describe and analyse the dualism of management (top-down approach and Madrasah-Based Management/MBM) in the implementation of the education subsidy programme for orphans, with a focus on developing madrasah management that is responsive to the local needs of the community. This research employed a qualitative approach using a case study design conducted at Al-Khairiyah Citangkil Private Madrasah Aliyah, Cilegon, Banten. The findings indicate that the educational subsidy programme provides significant opportunities for orphans and economically disadvantaged students to access quality education. On the one hand, the top-down management approach ensures programme standardisation, policy control, and financial accountability. On the other hand, Madrasah-Based Management allows contextual adaptation to local needs and institutional conditions, thereby enhancing the effectiveness and relevance of educational services. This study implies that effective synergy between top-down policy frameworks and the flexibility of Madrasah-Based Management is essential for developing an inclusive and sustainable education system that empowers madrasahs to respond to the educational needs of their local communities.